Capital Structure and Sustainability Performance: Leverage Modification through Equity Disaggregation - Arisyahidin, Arisyahidin; Kusuma, Marhaendra; Ahamad, Abdul Hadi Bin; Nunes, Mariano (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2025)
This study investigates the impact of capital structure on sustainability performance, with operating performance and earnings management acting as moderating variables. Capital structure is measured using the debt-to-equity ratio, considering total equity and equity attributable to each owner. The analysis is based on financial statement data and ESG scores from 921 companies across 11 Asian countries, covering 2,763 firm-year observations between 2020 and 2024. Moderated regression analysis was applied to test the hypotheses. The findings show that capital structure positively affects sustainability performance, with operating performance strengthening this relationship and earnings management weakening it. These patterns remain consistent during and after the COVID-19 pandemic and are confirmed when alternative measures are used. The theoretical implications highlight the importance of equity disaggregation, supporting the presentation of attributable equity in leverage calculations when assessing its effect on sustainability performance, alongside the moderating roles of operating performance and earnings management. The originality of this research lies in modifying the leverage calculation by disaggregating equity according to the attributable equity policy and examining its influence on sustainability performance, while also testing the moderating effects of operating performance and earnings management.